Theology of Education in the Second Vatican Council’s Gravissimum Educationis - Stuart Nicolson (Theology and Philosophy of Education, 2022)
Theology of education regards the growth in the journey with God and being with God and others. Gravissimum Educationis (GE) calls for moral learning in education, and specifically Christian education so Christians grow in God, become more Christ-like (theosis) and an active participant in society, thus bringing Christianity to the world. The document also encourages different theological means of communicating the faith to educate Christians and reach out to others. This paper identifies both of these themes in GE, focusing on the early sections of the document.